FRI0368 Autologous stem cell transplantation with a conditioning regimen using thiotepa in patients with systemic sclerosis and cardiac manifestation. (23rd January 2014) - Henes, J. C.; Horger, M.; Schmalzing, M.; Vogel, W.; Kanz, L.; Koetter, I.
Abstract : Background: Autologous stem cell transplantation (aSCT) has proven to be effective in systemic sclerosis (Ssc). Cyclophosphamide (CYC) is one cornerstone for conditioning treatment but is known to be cardiotoxic. Two case reports describe the successful use of thiotepa 1, 2 . Objectives: To find an alternative, less cardiotoxic conditioning regimen Methods: Retrospective analysis of 6 patients with Ssc who received aSCT using a conditioning therapy with a reduced dose of CYC (2x50mg/kg bodyweight) + thiotepa (2x5mg/kg bodyweight) + rabbit antithymocyte globulin. Modified Rodnan skin score (mRSS), as well as CT histography – measuring median lung density (MLD, Hounsfield units) as well as total lung volume and high attenuation value (HAV) were used to assess efficacy after 6 and 12 months. For safety parameters we assessed the time to engraftment (>500 neutrophils and >20.000 thrombocytes/µl), severe complications as well as troponin I (normal or elevated) and echocardiography (left ventricular function and systolic pulmonary arterial pressure (PAPsys >30mmHg = pathologic). Results: Four male and 2 female patients with a median age of 41years (19-57) and a disease duration of 1.8 years (0.5-4.5) were transplanted for progressive Ssc despite CYC pulse pre-treatment. Indication for the alternative treatment regimen were biopsy proven myocardial fibrosis in all patients plus pathologic 24h-ECG (n=4), echocardiography (n=2) or cardio MRI (n=2). All patients have had elevated troponin values in the past and received an implantable cardioverter defibrillator in preparation for aSCT. The median time to regeneration was 21 and 20 days for neutrophils and thrombocytes. Two patients, who were transplanted at the same day, experienced a severe aspergillus pneumonia which was successfully treated with antimycotic therapy. No transplant-related mortality was observed. The median mRSS significantly reduced from 26.5 to 18 ( p=0.028) and 17.5 at month 6 and 12, respectively. Using lung CT histography, MLD as well as total lung volume and HAV improved during the first year. One patient, initially having responded, experienced a severe progression of skin thickening and PapSys after 9 months. He died 1.6 years after aSCT due to progressive disease. Another patient had a mild alveolitis after 1.5 years with a which was successfully treated with 4 pulses CYC. All other patients show an ongoing response to treatment without sign of progression. This leads to a progression free survival rate of 66.6% during the median follow up period of 1.4 (0.5-3.8) years. In none of the patients elevation of troponin or reduction of left ventricular function could be assessed during the median follow up period of 1.4 years. Conclusions: A conditioning regimen with a reduced CYC dose and partial substitution by thiotepa is feasible and seems to be effective. The two cases of aspergillus infections must be watched carefully; interestingly they appeared during the same time, so air contamination can be discussed. Our preliminary experiences led to our currently recruiting protocol with the use of this regimen in patients with Ssc and cardiac involvement. References: Komatsuda A et al. Tohoku J Exp Med 2006;209:61-7. Giorgetti F et al. Reumatismo 2004;56:51-6. Disclosure of Interest : None Declared